Clinical practice guidelines for pseudoxanthoma elasticum (2017): Clinical Practice Guidelines for Pseudoxanthoma Elasticum Drafting Committee. Issue 3 (12th January 2022) - Iwanaga, Akira; Utani, Atsushi; Koike, Yuta; Okubo, Yumi; Kuwatsuka, Yutaka; Endo, Yuichiro; Tanizaki, Hideaki; Wataya‐Kaneda, Mari; Hatamochi, Atsushi; Minaga, Kosuke; Ogi, Tomoo; Yamamoto, Yosuke; et al.
Abstract: Pseudoxanthoma elasticum (PXE) is a progressive hereditary disease that affects tissues such as the skin, retina, blood vessels, and gastrointestinal tracts. Therefore, comprehensive medical care across clinical departments specialized in specific organs is needed to provide the best clinical practices to PXE patients. The Japanese version of clinical guidelines developed by the Japanese Dermatological Association was published in 2017, and aimed to promote equal accessibility of PXE‐related medical care. Here, the English version of Japanese guideline is reported, and is intended to be worldwide reference for medical care of PXE.